FEA on the biomechanical behavior of immediately loaded implants with different sizes - Raluca Monica Comaneanu; Teodora Mihali; Cherana Gioga; Anna Maria Pangica; Paula Perlea; Costin Coman; Violeta Hancu; Oana Botoaca; Monica Voiculeanu; Mihail Tarcolea (Amaltea Medical Publishing House, 2023)
Objectives. The purpose of this research was to study, in the case of immediate loading, the biomechanical effect produced by the length of the implants. Material and method. The study material was a CBCT analysis performed on a patient from one dental office in Bucharest. An segment of edentulous mandibular bone was selected from the CBCT, which was processed with Mimics Innovation Suite, respectively Mimics and 3-matic. After processing the bone segment, two implants of the same manufacturer, with identical design, but different length - 10 and 13 mm respectively, were selected from the BIOMAT database. To simulate immediate loading, the bone-implant interface was not blocked and the mandible was defined with properties that characterize a bone with moderate density. A perpendicular masticatory force of 200N was applied to each of the two implants. The software ANSYS calculated the minimum, maximum values and their geometric means for the possible stresses produced on both the shorter implant (10 mm) and the longer implant (13 mm). Results. In the case of short implants, higher average stresses develop along the entire length of the implant, towards the vestibular bone plate, while in the case of long implants the higher stress seems to be cantoned towards the apical side. Conclusions. The present study shows that, in the case of immediate loading, the use of longer implants (13 mm) reduces by more than 50% the geometric mean of the stresses to which the bone-implant interface is subjected than in the case of the use of shorter implants (10 mm). In both types of implants, higher stresses occur at the level of the screw fixing the abutment in the implant.